Comparison of intra-session reliability of force-velocity-power variables between a horizontal dynamic leg press device and vertical jump tests - Takuya Nishioka; Shota Yamaguchi; Daiki Hajima; Yasuhiro Kunita; Takayuki Inami (PLoS ONE, 2025)
This study aimed to compare the intra-session reliability of force-velocity-power variables obtained from a horizontal dynamic leg press device (HDLPD) and vertical jump tests. Nineteen male field hockey players performed maximal leg extension movements in HDLPD under a wide range of available load conditions (100, 120, 140, 160, 180, and 200% body weight [BW]), followed by squat jumps (SJ) and countermovement jumps (CMJ) under unloaded (0 kg), moderate- (22.0 ± 4.6 kg), and high-loaded (43.9 ± 9.2 kg) conditions. The peak and mean values of force, velocity, and power derived from the HDLPD, SJ, and CMJ were calculated. The HDLPD showed acceptable intrasession reliability for all experimental outcomes (intraclass correlation coefficient [ICC] = 0.845 to 0.974, coefficient of variation [CV] = 0.43% to 4.52%). The outcome variables during SJ and CMJ had acceptable intra-session reliability, except for the relative reliability of some variables (ICC = 0.588–0.973, CV = 1.19%–8.38%). The results of this study showed that the HDLPD has high intrasession reliability in measuring force-velocity-power variables for maximal leg extension performance. In addition, for some force-velocity-power variables, HDLPD can provide more reliable measurements than vertical jumps. Therefore, the HDLPD can be useful for practitioners who want to reliably measure leg extension strength, speed, and power outcomes.